Review: proteins c-Myc and Myc-nick as potential targets for the melignant melanoma treatment - Maryniuk, G.; Stepanov, G.; Oleynik, K.; Selyvanska, I.; Tereshchenko, L.; Dubna, Y. (Journal of Education, Health and Sport, 2023)
Malignant melanoma is the most aggressive and life-threatening skin cancer with increasing incidences over the past decades. Despite accounting for only 4 % of all skin cancers, melanoma confers 80 % of skin cancer induced death. The underlying cause of melanoma progression and metastasis is poorly understood. Myc is a very strong proto-oncogene and it is very upregulated in many types of cancers. c-Myc protein is a transcription factor that activates expression of many genes. It drives cell proliferation, plays a very important role in regulating cell growth, apoptosis and differentiation. High c-Myc expression is associated with tumor metastasis and poor prognosis in human melanoma. Full-length c-Myc is converted into Myc-nick by calcium-dependent on cytosolic proteases that are members of the calpain family. In connection with the key role of the cytoplasmic protein Myc-nick in the autophagy activativation, increasing the resistance to chemotherapy and overall survival of tumor cells, it can be a target for treatment tumors under the conditions of c-Myc overexpression. That fact that the expression of Myc-nick increases the survival of cells after UV radiation can indicate the key role of the Myc-nick in tumorogenesis of melanoma cells.